The Relationship Between Crime Reporting and Police: Implications for the Use of Uniform Crime Reports - Levitt, Steven D. (Journal of quantitative criminology, 1998)
Empirical studies that use reported crime data to evaluate policies for reducing crime will understate the true effectiveness of these policies if crime reporting/recording behavior is also affected by the policies. For instance, when the size of the police force increases, changes in the perceived likelihood that a crime will be solved may lead a higher fraction of victimizations to be reported to the police. In this paper, three data sets are employed to measure the magnitude of this reporting bias. While each of these analyses is subject to individual criticisms, all of the approaches yield similar estimates. Reporting bias appears to be present but relatively small in magnitude: each additional officer is associated with an increase of roughly five Index crimes that previously would have gone unreported. Taking reporting bias into account makes the hiring of additional police substantially more attractive from a cost–benefit perspective but cannot explain the frequent inability of past studies to uncover a systematic negative relationship between the size of the police force and crime rates.